Job Satisfaction and Teacher Retention in Selected Senior High School in Ghana (International Journal of Scientific Research and Management (IJSRM), 2020)
The study investigated into job satisfaction and teacher retention. Fifty teachers who were made up of 36 males and 14 females were randomly sampled. Questionnaire was used in the data collection. The data gathered was scored with a likert scale. The raw scores were entered into the Statistical Package for the Social Sciences(SPSS) Software System. The first research question sought to find out what factors contributed to job satisfaction among teachers at Zuarungu Senior High School. A good number of the teachers agreed to factors such as salary, accommodation and administrative support contributing to job satisfaction. The second research question was to find out in what ways job dissatisfaction affected teachers’ performance in Zuarungu Senior High School. Majority agreed that absenteeism, refusal to do assigned duties, not setting and marking of exams timely are some of the effects of job dissatisfaction. Research question three was to find out what factors influenced teachers’ decision to quit teaching in Zuarungu Senior High School. The teachers responded to the following factors that would compel them to quit teaching; no provision of accommodation for teachers and non-payments of allowances due them. Research question four was to find out effective ways of attracting and retaining teachers in Zuarungu Senior High School. The teachers agreed that provision of accommodation, payment of allowances and soft loans would attract them to the school. The analysis was summarized and concluded that employees, especially teachers leave the teaching field because they are not satisfied with theirjob as a result of poor working conditions. They study recommended that Ghana Education Service should provide goodworking conditions like provision of accommodation and timely payment of allowances to mitigate their decision to quit teaching which in the long run affects the performances of the innocent school children. It was suggested that the research should be widened tocover more schools in the municipality